Integrating Blockchain and AI in Business Operations to Enhance Transparency and Efficiency within Decentralized Ecosystems - Rakhmansyah, Mohamad; Hadi, Muhammad Saiful; Junaedi, Sausan Raihana Putri; Ramahdan, Fikri Arsla; Putra, Souza Nurafrianto Windiartono (ADI Publisher, 2025)
This study explores the integration of Blockchain and Artificial Intelligence (AI) technologies in business operations, aiming to enhance transparency and operational efficiency within decentralized ecosystems. Blockchain offers so- lutions to trust issues in business systems through its secure and transparent characteristics, while AI plays a pivotal role in data analysis and automating decision-making. This study uses a qualitative research approach, incorporat- ing case studies and expert interviews to examine the potential and challenges of applying these technologies. The results show that integrating Blockchain and AI accelerates business processes, reduces operational costs, and fosters trust among stakeholders in decentralized ecosystems. However, challenges such as technology adoption, scalability, and initial implementation costs remain signif- icant barriers. This research contributes to the development of more efficient and transparent operational strategies through the application of advanced tech- nologies, and provides a foundation for future research on the impact of these technologies in global business sectors.